Implemetasi Pengungkapan Corporate Social Responsibility pada Perusahaan Sektor Industri Dasar dan Kimia - Hartono, Edi (Jurnal Kajian Akuntansi, 2018)
AbstractAny company whose business activities in a sustainable manner relating to the utilization of natural resources either directly or indirectly required to submit a report of social responsibility more widely in which corporate social responsibility (CSR) is a voluntary activity undertaken by the company as a form of corporate responsibility for internal and external companies in the field of social and environmental. This study aims to analyze implementation corporate social responsibility disclosure The research method used is descriptive statistic method. The sample selection based on Purposive Sampling amounted to 77 companies of basic and chemical industry sectors listed on BEI in 2013-2015. Data analysis in this research using quantitative descriptive analysis. The results of the study indicate that the overwhelming majority paid more attention to the economic aspects that could support the creation of corporate profitability. While viewed from the aspect of the planet or the environment, indicating that the activity and disclosure of environmental indicators is still quite low.Keywords: CSR disclosure; Triple bottom line theory; Legitimacy theory; Stakeholder theory.